Cabot reports revenue growth in 4Q and fiscal year 2014. Issue 2 (February 2015) - Unknown
Abstract : Boston-based Cabot Corp reported year-on-year increases in net sales for both its fourth quarter and full fiscal year (FY) ended 30 September 2014. In 4Q 2014, the company achieved net sales of US$911 million, up 1.7% compared with net sales of $896 million the previous year. For FY 2014, net sales rose 5.5% to $3.65 billion compared with $3.45 billion a year earlier.